Tinjauan Yuridis Terhadap Kewenangan Pengadilan Negeri dalam Mengadili Perbuatan Melawan Hukum Yang Dilakukan Oleh Anggota KPU dalam Proses Penyelenggaraan Pemilihan Umum - Gahtan Hanu Cakita; Muhammad Jarnawansyah (SENTRI: Jurnal Riset Ilmiah, 2026)
This research examines the authority of the District Court (Pengadilan Negeri) in adjudicating unlawful acts (perbuatan melawan hukum) committed by members of the General Election Commission (KPU) during the electoral process in Indonesia. As a state administrative body, the KPU holds a strategic role in ensuring democratic and fair elections. However, in practice, administrative errors, abuse of authority, or negligence by KPU members may cause material or immaterial losses to election participants or the public, thereby constituting unlawful acts under Article 1365 of the Indonesian Civil Code. This raises a fundamental legal question: whether such acts fall under the jurisdiction of the District Court as a general civil court, or whether they should be resolved through special mechanisms such as the Election Supervisory Body (Bawaslu), the Election Organizers Honorary Council (DKPP), or the State Administrative Court (PTUN). This normative juridical research employs a statutory approach and literature study to analyze legal norms, doctrines, and relevant court decisions. The findings indicate that the District Court has the authority to adjudicate unlawful act claims against KPU members when the act causes personal civil losses, is separable from formal administrative decisions, and does not fall within the exclusive jurisdiction of administrative or electoral dispute resolution mechanisms. This research contributes to providing legal clarity and strengthening the accountability of election organizers in Indonesia.